Pengaruh Adverting, Brand Awareness Dan Brand Trust Terhadap Keputusan Pembelian Produk Merek Make Over (Studi Pada Mahasiswa FEB UM Metro) - Dewi, Gendhis Haningkas Tinika; Fitriani, Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2021)
Make Over is a cosmetic brand released by PT. Paragon Technology and Innovation, which created a cosmetic brand that is well-known in Indonesia for being halal, as quoted from IDNTimes. Make Over products, which initially were only known for a few products, did advertising and increased brand awareness in consumer purchasing decisions, making people aware and knowing that Make Over products vary. After the increase in sales of Make Over products, it is necessary to make consumers believe that Make Over products are good and not dangerous, when consumers believe, consumers will repurchase the product. The purpose of this study was to determine the significant influence of Advertising, Brand Awareness and Brand Trust on the Purchase Decision of Make Over Brand Products. In this study using primary data and secondary data, the research method used accidental sampling is a sampling technique by chance, namely respondents who accidentally meet the researcher and can be used as samples if the person is suitable as a data source, namely students of FEB Muhammadiyah Metro University, with a sample size of 70 people. The data analysis technique used is validity test, reliability test, normality test and linearity test. Testing the analysis model in this study using multiple linear regression analysis, T test, F test and R determination. Based on the results of research using the T test, it is found that advertising has a positive and significant effect on the decision to buy a make over brand product, brand awareness has a positive and significant effect on the decision to buy a make over brand product and brand trust has no significant effect on the decision to buy a make over brand product From the F Advertising test, Brand Awareness and Brand Trust together have a positive and significant effect on the Purchase Decision for Brand Make Over Products. Keywords- Advertising, Brand Awareness, Brand Trust and Purchasing Decisions